Er mere meditation relateret til større behandlingseffekter? – Empirisk baserede anbefalinger til en mere kontekstuel meditationsforskning og interventionspraksis - Jensen, Christian Gaden; Holde, Louise Victoria Alliverti (Psyke & Logos, 2016)
Meditation is increasingly applied in health promotion and clinical interventions although the influence of meditation during multimodal interventions is unclear. Even among meditation-based interventions (MBI), theories and recommendations concerning meditation vary substantially. Our primary purpose is to discuss from an empirical base if MBI-participants’ amount of meditation practice is a substantial factor for the treatment effects. We investigate this especially by reviewing MBI-research on dose-effect relationships between meditation and outcome changes, and neuroimaging studies of meditators and MBI-participants. The clinical evidence shows that participants’ amount of meditation practice is not consistently related to treatment effects. Neuroscientific studies support this notion, since previous meditation practice has not been consistently or specifically related to structural or functional neural measures for MBI-participants or experienced meditators. The inconsistent dose-effect findings, however, do not lead us to discard meditation as a potentially important aspect of psychosocial interventions. Previous research is methodologically criticizable due to a lack of active control groups, studies investigating the importance of meditation as a function of participant characteristics, and qualitative studies of the experienced significance or quality of the meditation practices. In addition, meta-syntheses of qualitative studies of processes of change during MBI do conclude that meditation is experienced as effective, but in complex, systemic interactions with other treatment aspects. More complex models concerning the significance of meditation practices for different participants and clinical areas are thus needed. We present a contextual, functional and pragmatic approach to the application of meditation and provide recommendations for future research and practice.